Concern about the human health implications of marine biodiversity loss is higher among less educated and poorer citizens: Results from a 14-country study in Europe - Sophie M. C. Davison; Mathew P. White; Sabine Pahl; Tim Taylor; Angel Borja; Oonagh McMeel; Paula Kellett; Bethany R. Roberts; Lora E. Fleming (Frontiers in Marine Science, 2023)
Introduction Marine biodiversity loss has direct and indirect effects on human health and wellbeing. Recent European data suggest that the public is aware of this, identifying marine biodiversity protection as its top research priority in terms of oceans and human health, rated higher than issues such as plastic, chemical, and microbial pollution. Methods The current study aimed to better understand key sociodemographic and personality predictors of concern about marine biodiversity loss and the desire for more research into marine biodiversity protection, in an attempt to support communication efforts targeting specific sectors in society. Data were drawn from nationally representative samples of 14 European countries (n = 14,167). Results Results show greater concern about marine biodiversity loss and support for more research into marine biodiversity protection by older adults, females, and individuals: (i) without (vs. with) a university degree; (ii) with lower (vs. middle) incomes; (iii) who identified as politically left-wing; (iv) who visited the coast more often; and (v) those with more open, agreeable and conscientious personalities. Discussion These results suggest that, although concern and research support are generally high among European citizens, policy makers and communicators need to take into consideration individual-level variation.